Ubiquinone Ameliorates Hippocampus Injury Induced by Cerebral Ischemia/Reperfusion - Faraji, Mahsa; Nadia Sharifi, Zahra; Nazarnejad, Mohammad Mahdi; Movasseghi, Shabnam; Akbarzadeh, Saman (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Apoplexy is known as a critical issue all over the world and certain parts of the brain are more sensitive to Ischemia/cerebral reperfusion such as the hippocampus. Coenzyme Q10 is a powerful anti-oxidant, which helps in cells membrane durability. Aim: This study attempts to find the effect of coenzyme Q10 on the change of hippocampal area texture after cerebral reperfusion/Ischemia. Methods: Twenty-four male Wistar rats were organized into 4 groups of six including control, Ischemia, vehicle and experimental groups, with 100 mg /Kg of coenzyme Q10. Coenzyme Q10 was given to the rats 5 days before and 3 days after Ischemia/reperfusion induction. Ischemia was done for 20 minutes by reciprocal blocking of carotid arteries. The rat’s brains were removed and stained by applying the chrysalis fast violet method. The number of viable cells of the hippocampal regions of all 4 groups was counted by Imaging-Pro-Plus software. Statistical analysis of the data was then accomplished by one-way ANOVA and Tukey's test. Results: Findings revealed that the number of viable cells in CA2 and CA3 area reduced following ischemia induction. Whereas, there was no notable change between the control and experimental groups in terms of cells numbers. Besides, there was no remarkable change between the control, experimental and ischemia groups in terms of the number of cells within CA4 area. Conclusion: The results support the use of coenzyme Q10 as a neurotrophic substance and as an adjunctive therapy in patients at risk for ischemic stroke.